Description of Antaeola rhinosa sp. nov. (Lepidoptera: Tortricidae: Olethreutinae) from Thailand - Muadsub, Sopita; Pinkaew, Nantasak (Zootaxa, 2023)
The genus Antaeola has remained monotypic since its description by Diakonoff in 1973. A new species, Antaeola rhinosa sp. nov., is described and illustrated from Thailand. The new species can be distinguished from A. antaea (Meyrick) by facies and features of the male and female genitalia.